Tinjauan Literatur: Hubungan Obesitas dan Infertilitas pada Pria Usia Produktif: A Literature Review: Association between Obesity and Infertility in Productive-Aged Men - Putri, Allisa Nadhira Permata Arinda; Nadhiroh, Siti Rahayu (Amerta Nutrition, 2024)
Background: Obesity is a worldwide epidemic problem that is increasing continuously. Obesity negatively affects several functions in the body, including reproductive function (fertility). The prevalence of infertile couples in Indonesia in 2013 was 15-25% with male infertility accounting for 25-30% of total infertility cases. Objectives: This study aimed to determine the association between obesity and infertility in productive-aged men. Methods: The research results from eight observational studies gathered in accordance with inclusion criteria, credible literature on the topic of obesity and male infertility, were examined in this study using the literature review method. Additionally, the exclusion criteria encompassed references that were not accessible in full text and related to animal studies. Discussion: Obesity can have a direct or indirect effect on male fertility through several mechanisms of hormonal profile changes. Moreover, the excessive conversion of androgens to estrogens caused by obesity can lead to an increase in aromatase activity and subsequent reproduction; this imbalance ultimately results in lower-quality sperm. Additionally, obesity causes high plasma leptin levels. Furthermore, sperm plasma membrane fluidity, impairing sperm motility, and increasing sperm deoxyribonucleic acid (DNA) damage are all negatively affected by leptin-induced increases in oxidative stress and the uncontrolled production of reactive oxygen species (ROS). Conclusions: An increased BMI increases the risk of decreased sperm parameters, which indicates a higher level of infertility in men. Obese men may increase the risk of changes in sperm parameters both quantitatively (volume, number, and concentration) and qualitatively (motility, morphology, and sperm DNA).